Knowledge Management as a Business Strategy of a Learning Organisation - Rudančić, Andreja (Array, 2021)
Today, knowledge management is used as part of a business strategy by which an organisation adapts to rapid changes in society and the business world, by which it not only becomes more competitive but also achieves goals and remains successful. Organisations have become aware of the importance of the lifelong learning concept. It should be noted that knowledge management is in close synergy with human resource management in the organisation. To achieve the scientific value of the paper, the authors have conducted empirical research by using a survey questionnaire in which the elements of a learning organisation were investigated, along with the implementation of knowledge on the selected organisational model. The synthesis of the results and conclusions of this research will be used to formulate specific critical recommendations and valuable guidelines indicating possible areas of improving the level of learning organisation and motivation to learn, which indicates potential ways and approaches to knowledge management.